2008
DOI: 10.1177/1548051808320984
|View full text |Cite
|
Sign up to set email alerts
|

The Interactive Effects of Centralization on the Relationship Between Justice and Satisfaction

Abstract: The current study examines the effects of centralization on the relationship between organizational justice and job satisfaction using referent cognitions theory as a theoretical foundation. The sample consists of 489 members of the National Association of Purchasing Managers. Results indicate that the relationships between procedural, distributive, and interactional justice and job satisfaction are stronger under conditions of high centralization. Directions for future research and implications for managers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
1
8
0
2
Order By: Relevance
“…Consistently, a number of contemporary studies have demonstrated that less decision making authority at the frontline is positively related to firm performance (Andrews et al, 2008;Chang and Harrington, 2000;Richardson et al, 2002). Similarly, organizational stability and operational efficiency with formalized rules and procedure has also been demonstrated as important for firm growth (Caruana et al, 1998;Quinn and Cameron, 1983;Sine et al, 2006).…”
Section: Structure and Effectivenessmentioning
confidence: 87%
“…Consistently, a number of contemporary studies have demonstrated that less decision making authority at the frontline is positively related to firm performance (Andrews et al, 2008;Chang and Harrington, 2000;Richardson et al, 2002). Similarly, organizational stability and operational efficiency with formalized rules and procedure has also been demonstrated as important for firm growth (Caruana et al, 1998;Quinn and Cameron, 1983;Sine et al, 2006).…”
Section: Structure and Effectivenessmentioning
confidence: 87%
“…Tais dados mostram-se congruentes com os diversos estudos anteriores que também têm demonstrado que as percepções de justiça processual (Andrews et al, 2008;Clay-Warner et al, 2005;Fields et al, 2000;Harvey & Haines III, 2005;Lawson et al, 2009;Suliman, 2007), assim como as percepções de justiça interpessoal (Lawson et al, 2009) e de justiça distributiva (Andrews et al, 2008;Clay-Warner et al, 2005;Fields et al, 2000;Harvey & Haines III, 2005;Lawson et al, 2009;Suliman, 2007) caracterizam-se como preditoras positivas da satisfação no trabalho. Por outro lado, eles divergem das pesquisas (Lawson et al, 2009) que têm demonstrado o papel preditor positivo desempenhado pelas percepções de justiça informacional na satisfação no trabalho.…”
Section: Discussionunclassified
“…Os estudos sobre as percepções de justiça organizacional e a satisfação no trabalho têm evidenciado que as percepções de justiça distributiva associam-se positivamente à satisfação no trabalho (Andrews, Baker, & Hunt, 2008;Clay-Warner, Reynolds, & Roman, 2005;Fields, Pang, & Chiu, 2000;Harvey & Haines III, 2005;Lawson, Noblet, & Rodwell, 2009;Suliman, 2007), o mesmo ocorrendo com as percepções de justiça processual (Andrews et al, 2008;Clay-Warner et al, 2005;Fields et al, 2000;Harvey & Haines III, 2005;Lawson et al, 2009;Suliman, 2007), de justiça interacional (Andrews et al, 2008;Suliman, 2007), de justiça interpessoal (Lawson et al, 2009) e de justiça informacional (Lawson et al, 2009). Contudo, quando se comparam as percepções de justiça distributiva e de justiça processual, esta última tem se mostrado melhor preditora do bem-estar no trabalho (Gilliland & Chan, 2001).…”
Section: Justiça Organizacional E Bem-estar Laboralunclassified
“…A body of literature concerning justice indicates that interactional justice has critical influence on employees' attitudes (Ambrose et al , 2007). Typical workplace attitudes examined are organizational commitment, job satisfaction, and trust (Ambrose et al , 2007; Andrews et al , 2008; Molleman, 2009; Stumpp et al , 2009). Studies examining the effects of interactional justice on attitudes show positive relationships between interactional justice and trust in management and between interactional justice and the attitude toward a supervisor's decision (Ambrose and Schminke, 2003; Bies and Shapiro, 1987).…”
Section: Hypotheses Developmentmentioning
confidence: 99%